Back Matter - JTSiskom Volume 6 Nomor 1 Tahun 2018 - JTSiskom, Editor in Chief (Jurnal Teknologi dan Sistem Komputer, 2018)
This article contains back-matter of JTSiskom Volume 6 Issue 1 Year 2018, which includes the author's index, author guidelines, copyright notice and its transfer agreement, publication ethics statements and journal content licenses.